PENGGUNAAN SOCIOGRAM UNTUK MENGIDENTIFIKASI POLA JARINGAN SOSIAL PEMBELAJARAN MANDIRI MAHASISWA (Identification of Social Network of Student’s Independent Learning using Sociogram) - Yenni Angraini; Bagus Sartono; Dian Kusumaningrum (FORUM STATISTIKA DAN KOMPUTASI, 2012)
This paper presents a useful tool to help universities to increasing the level of their graduate outcome by using the information about social network among students. Such a quantitative tool is a sociogram which depicts how students interact with others. The graph can be easily generated when the pattern of the connectivity among individuals is known. We apply sociogram to portray the network of a class of students in Department of Statistics – Bogor Agricultural University which represent the way they interact when they want to discuss the academic related problems. We found some interesting results are practically valuable for the one who is responsible to the study result of the students. Some results are not new, but this approach could provide more informative features than conventional tables or such things.Keywords : sociogram, social network analysis